PENGARUH PENAMBAHAN DAUN KANGKUNG (Ipomoea aquatica) TERHADAP KUALITAS TELUR AYAM KAMPUNG - Supranoto Supranoto (Media Peternakan, 2021)
This study aimed to evaluate the effect of supplementing the diet with water spinach (Ipomoea aquatica) leaves on the egg quality of native chickens. The research was conducted at the Faculty of Animal Science, Universitas Wijayakusuma Purwokerto. A total of 72 native chicken hens aged 24 weeks were used in this study. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 6 replications. The treatments given were P0 (basal diet without water spinach leaves), P1 (basal diet + 5% water spinach leaves), P2 (basal diet + 10% water spinach leaves), and P3 (basal diet + 15% water spinach leaves). The observed variables included egg weight, egg shape index, shell thickness, yolk index, albumen index, Haugh Unit, and yolk color. The results showed that the addition of water spinach leaves had a significant effect (P0.05) on egg shape index, albumen index, and Haugh Unit. It was concluded that the addition of 10% water spinach leaves in the diet can improve the egg quality of native chickens.